Internal Management Challenges and Strategic Solutions in Communication Management Services: A Descriptive-Quantitative Approach - Yanqian, Xiao (International Journal of Sustainability and Advanced Integrated Research, 2025)
This study employed a descriptive-quantitative research design to examine internal management challenges within a communication services company. Utilizing statistical techniques such as mean and standard deviation, alongside thematic analysis, the research identified key concerns including communication inefficiencies, inconsistent leadership practices, and gaps in employee engagement. Data was gathered through a structured survey questionnaire distributed to 60 purposively selected respondents from departments including Management, Human Resources, Finance, and Legal. The combination of quantitative and qualitative methods provided a robust understanding of organizational dynamics, highlighting both operational strengths and areas needing improvement. Conducted in Beijing—a major business and cultural hub—the study explored how organizational structure, leadership behavior, and cultural factors intersect to shape internal performance. The findings reveal notable strengths in planning, goal alignment, and leadership clarity, but also indicate persistent challenges in operational efficiency, staff development, and gender diversity. Recommendations center on increasing female workforce participation, strengthening feedback systems, and fostering innovation through collaborative leadership. Strategic interventions were proposed to boost competitiveness, enhance internal processes, and create a more inclusive and productive work environment. Future researchers are encouraged to explore the underlying causes of gender imbalance and investigate the long-term effects of strategic interventions on employee retention and organizational performance.
Keywords: Employee Engagement; Future Research; Internal Communication; Leadership Practices; Organizational Management; Strategic Planning; Workplace Diversity